2015
DOI: 10.1517/14740338.2015.1085504
|View full text |Cite
|
Sign up to set email alerts
|

Do statins prevent acute kidney injury?

Abstract: The question of whether statins cause AKI remains unresolved. Evidence suggests that statins may both protect or harm kidneys acutely and that risk varies with the condition and the dose and type of statin used. However, any current adverse data should not deter prescription of statins in patients where there is clear evidence for either primary or secondary prevention of cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 98 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Statins have been shown to have anti-inflammatory effects by reducing the levels of inflammatory cytokines as well as circulating microparticles, which are involved in inflammatory cell activation (35). However, whether or not the use of statins preoperatively can decrease the incidence of CSA-AKI remains controversial (36-38); further studies are therefore needed.…”
Section: Discussionmentioning
confidence: 99%
“…Statins have been shown to have anti-inflammatory effects by reducing the levels of inflammatory cytokines as well as circulating microparticles, which are involved in inflammatory cell activation (35). However, whether or not the use of statins preoperatively can decrease the incidence of CSA-AKI remains controversial (36-38); further studies are therefore needed.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective case controlled studies found that statins reduced acute kidney injury in patients with contrast-induced nephropathy [ 92 , 93 ], whereas a prospective study did not find any beneficial effects [ 94 ]. Remarkably, a number of observational studies suggested that in the first few weeks and months of starting a statin, statins were associated with the early development of acute kidney [ 95 ]. Due to the adverse data and the lack of good prospective randomized controlled trials, there is no evidence that statins reduce the incidence of acute kidney injury.…”
Section: Introductionmentioning
confidence: 99%
“…[ 39 ] Statins have been shown to improve basal NO activity and NO-dependent endothelium-derived vasodilatation in healthy volunteers and in patients with heart disease. [ 40 ] They have also been shown to significantly ameliorate endothelial dysfunction in patients with carotid artery disease (CAD) via the regulation of endothelial NO synthase function and phosphatidylinositide 3-kinase/Akt signaling. [ 41 43 ] Atorvastatin increases NO availability, prevents the production of oxygen free radicals, and downregulates the expression of cyclooxygenase 2.…”
Section: Discussionmentioning
confidence: 99%